Information structuring in lead texts in online press – a comparative analysis of German and Polish - Filar, Magdalena (Papers in Linguistics, 2025)
The aim of the paper is to provide a description and comparative analysis of information structuring in Polish and German lead texts in daily press. The analysis follows the theoretical framework of the functional-cognitive approach in text linguistics, according to which the theme-rheme structure is defined as information schemata or patterns. Their description takes into account primarily the category of given/new information, as well as other factors, and focuses on a) the information structure of the sentence opening a lead text; and b) determining how such information is referenced in the text. The undertaken comparative analysis reveals similarities in the information structuring in informative lead texts (information pattern 1 and 2) in German and Polish, some similarities (introduction of initial text referents with cataphoric expressions, contrasting information in German and Polish texts), and differences in persuasive lead texts (moving the given information to the rheme position, co-existence of two information patterns within one text in Polish). The analysis shows that elliptical constructions and semantic condensation do not limit the information potential of text and their information value is pragmatically conditioned.